Second Victim Experience and Support Tool: cultural adaptation and psychometric evaluation in Italy. (30th September 2020) - Scarpis, E; Ruscio, E; Bianchet, B; Doimo, A; Moretti, V; Cocconi, R; Farneti, F; Castriotta, L; Quattrin, R
Abstract: Background: "Second victims" are defined as "healthcare workers (HCWs) involved in an unanticipated adverse patient event, who experienced professional and psychological distress". The Second Victim Experience and Support Tool (SVEST) is a survey developed and validated in the United States, which describes the experience of second victims. This study aims to perform the cross-cultural adaptation of the SVEST and to evaluate its psychometric characteristics in the Italian context. Methods: The translation and cross-cultural adaptation process was performed according to the World Health Organization's guidelines, from March to May 2019. Then HCWs involved in direct patient care (a potential second victim) were asked to complete the Italian version of SVEST in a validation survey, from June to November 2019 at the Academic Hospital of Udine. SVEST consists of 29 items, divided into 7 dimensions, 2 outcome variables and 7 support options. The IT-SVEST was assessed for internal consistency through Cronbach's α, for content validity with Content Validity Index for Scales (S-CVI) and for Item (I-CVI) and for construct validity with Confirmatory Factor Analysis (CFA). Results: Collected surveys were 349. Women were 79.4%. Nurses were 40.1%, 18.9% were doctors and 8.6% were residents. HCWs involved in a patients' adverse event were 205 (58.7%). Out of these, 66.3% were near misses. The internal consistency of the instrument was adequate in its overall evaluation with Cronbach α = 0.88 (95% C.I.=0.86). S-CVI was 0.94 and I-CVI was 0.70. The CFA results showed a good model fit for the nine-factor structure (chi2=676.18, 327 df, p < 0.001). Root Mean Squared Error of Approximation, Akaike's information criterion, Comparative Fix Index Tucker-Lewis Index values also suggested a good fit to the data. Conclusions: The Italian version of the SVEST (IT-SVEST) can be used to evaluate second victim experiences, demonstrating adequate validity, reliability and good psychometric properties. Key messages: Healthcare institutions need an instrument that can direct efforts to prevent and reduce the second victim experience. IT-SVEST is a reliable and valid instrument to obtain accurate information on second victim experience.